Accumulation and Distribution of Heavy Metals in Mangrove Vegetation of the Coastal of South Sulawesi - Heru Setiawan (Jurnal Ilmu Kehutanan)
Mangroves have ecological functions to absorb, transport and stockpile toxic materials, e.g., heavy metal from surrounding environment. This research aimed to know the accumulation and distribution of heavy metals, i.e. Lead (Pb), Cuprum (Cu) and Cadmium (Cd) in mangrove vegetation of South Sulawesi. Vegetation samples were collected from four research location, which were Tanjung Bunga Makassar, Tallo River Makassar, Pare-Pare Bay and Bone Bay. Distribution of heavy metals in mangrove tissues was devided into five areas: pneumatophora, cable root, young leaves, old leaves and twig. Heavy metal content in the samples was measured using Atomic Absorption Spectrophotometric (AAS). The results showed that the highest accumulation of Pb was derived from the sample in Tallo River with 36.1 ppm. The highest accumulation of Cu was derived from Tanjung Bunga Makassar with 42.8 ppm. The highest accumulation of Cd was derived from Tallo River with 29.3 ppm. The distribution of heavy metals in mangrove showed that the highest accumulation of Pb was found in the cable roots with 9.5 ppm. The highest concentration of Cd was found in the young leaf with 3.1 ppm. The highest concentration of Cu was found in the cable roots with 10.1 ppm. Generally, Avicennia marina is mangrove species that has the highest concentration of heavy metals with Pb 24.2 ppm, Cd 30.9 ppm and Cu 71.2 ppm.